Plant Transformation Technology Revolution in Last Three Decades - Vol. 1 : Historical Technology Developments in Plant Transformation. - Dan, Yinghui (Bentham Science Publishers, 2011)
Plant transformation technology has played a critical role in advancing biotechnology and fundamental research and evolved as a science. This book describes the breakthrough technologies in all aspects of plant transformation in the last 27 years, which have been contributed by the world leading experts in the field. This e-book is one of the first books that covers critical technologies in all aspects of plant transformation to plant biologists and molecular biologists from industrial, academic and governmental organizations. It should greatly benefit postdoctoral associates and graduate and.